Acceptability of HIV Oral Self-Test Among Men Having Sex With Men and Transgender Population: A Qualitative Investigation From Pune, India. (October 2020) - Rao, Amrita; Patil, Sandip; Aheibam, Sharmila; Kshirsagar, Prajkta; Hemade, Pranoti; Panda, Samiran
Globally HIV-self-test is considered as an important tool to end AIDS. However, several countries, including India, are yet to adopt such a strategy. Against this background, we conducted a qualitative inquiry exploring acceptability of an HIV-oral-self-test (HIVOST) among MSM and TG communities in the district of Pune, India. Discussions were facilitated around an HIVOST kit developed in-country. Most of the participants expressed familiarity with the concept of self-test. They realised that confirmatory diagnostic test would be required following a positive HIVOST screening result. Discrimination from health care workers, crowded environment, lack of privacy and delay in getting reports were hurdles faced during HIV testing at public healthcare facilities. Contrastingly, quick results, painless technique and no-blood-draw were perceived advantages of HIVOST. Innovative suggestions were obtained on how-to-do instruction modalities, kit distribution venues and redressing of apprehensions. Such qualitative responses indicated interest and encouraging level of acceptance around HIVOST among study participants.